2016
DOI: 10.5606/archrheumatol.2016.5697
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Sexual Dysfunction in Females With Ankylosing Spondylitis

Abstract: Objectives: This study aims to evaluate sexual function in females with ankylosing spondylitis (AS), compare them with healthy controls, and demonstrate the effects of AS on female sexual functions. Patients and methods: Fifty-four AS patients (mean age 39.33±8.57 years; range 20 to 55 years) and 56 similar aged healthy controls were included in the study. Depression levels and sexual functions of all participants were evaluated by the Beck Depression Inventory and Female Sexual Function Index (FSFI), respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…Descriptive characteristics of the 55 included studies are summarised in Table 1. Of the included studies, 50 (90.1%) were quantitative, (7,9,19,27,(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)79,81,82,(84)(85)(86)(87)(88)(90)(91)(92)(93)(94)(96)(97)(98)(99)(100)(101)(102)(115)(116)(117)(118)(119)(120)(121) five (9.1%) were qualitative (77...…”
Section: Search Results and Description Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Descriptive characteristics of the 55 included studies are summarised in Table 1. Of the included studies, 50 (90.1%) were quantitative, (7,9,19,27,(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)79,81,82,(84)(85)(86)(87)(88)(90)(91)(92)(93)(94)(96)(97)(98)(99)(100)(101)(102)(115)(116)(117)(118)(119)(120)(121) five (9.1%) were qualitative (77...…”
Section: Search Results and Description Of Included Studiesmentioning
confidence: 99%
“…(8) Four of the qualitative studies used focus groups or semi-structured interviews, (80,83,89,95) while all the quantitative studies used patient-reported questionnaires. (7,9,19,22,27,(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)79,81,82,(84)(85)(86)(87)(88)(90)(91)(92)(93)(94)(96)(97)(98)(99)(100)(101)(102)(115)(116)(117)…”
Section: Search Results and Description Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Kobelt et al [ 12 ] found that age, sex, well-being, physical fitness, and mood were significant predictors of sexual activity in RA. Sexual dysfunction also correlated with pain, depressive mood, and degree of motor activity, and did not correlate with the BASDAI (Bath Ankylosing Questionnaire) – the main method of assessing the disease activity [ 18 ].…”
Section: The Impact Of Reumatic Diseases On the Sexuality Of Patientsmentioning
confidence: 99%